2017
DOI: 10.1016/j.jpeds.2016.08.101
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Sleeve Gastrectomy in Obese Adolescents on Nonalcoholic Steatohepatitis and Hepatic Fibrosis

Abstract: LSG was more effective than lifestyle intervention, even when combined with intragastric devices, for reducing NASH and liver fibrosis in obese adolescents after 1 year of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 28 publications
3
67
0
Order By: Relevance
“…From a comorbidity standpoint, studies have noted an 85% to 95% remission in T2D, a 64% to 73% resolution of dyslipidemia, and a 75% remission in hypertension . Importantly, bariatric surgery improves functional mobility and reduces musculoskeletal pain , favorably alters levels of adipokines and cytokines , improves insulin sensitivity and beta‐cell function , improves kidney function and albuminuria , reduces nonalcoholic hepatic steatohepatitis , and improves weight‐related quality of life . Moreover, a high proportion of youth are able to sustain weight loss long term, which should be an expectation given the risks and invasive nature of the procedure .…”
Section: Current State Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…From a comorbidity standpoint, studies have noted an 85% to 95% remission in T2D, a 64% to 73% resolution of dyslipidemia, and a 75% remission in hypertension . Importantly, bariatric surgery improves functional mobility and reduces musculoskeletal pain , favorably alters levels of adipokines and cytokines , improves insulin sensitivity and beta‐cell function , improves kidney function and albuminuria , reduces nonalcoholic hepatic steatohepatitis , and improves weight‐related quality of life . Moreover, a high proportion of youth are able to sustain weight loss long term, which should be an expectation given the risks and invasive nature of the procedure .…”
Section: Current State Of Treatmentmentioning
confidence: 99%
“…Unfortunately, like obesity, NAFLD is notoriously challenging to treat in both adults and pediatric populations. To date, only bariatric surgery and treatment with pioglitazone (which produces weight gain) in adults have been shown to be effective in improving NAFLD, leaving a tremendous gap for future research considerations.…”
Section: The Future Of Pediatric Severe Obesity Treatmentmentioning
confidence: 99%
“…A total of 36 studies were found that met the search criteria. The majority of studies were reviews ( n = 16, Table ), 8 were observational, 7 were case‐control studies, 3 were quasi‐experimental/case‐control studies, and 2 were RCTs (1 was a methods paper only) (Table ). No studies that tested the combination of pharmacotherapy interventions with MBS were found.…”
Section: Resultsmentioning
confidence: 99%
“…62 Melania Manco et al, found 100% improvement of NASH in adolescents, one year after SG and in their study, SG was most effective than lifestyle change and intragastric weight loss device. 41 Another study resulted in improvement of liver steatosis (66.6%), fibrosis (68%) and NAFLD activity score, 3 months after SG.…”
Section: Researchmentioning
confidence: 99%
“…5,62 Bariatric surgery procedures as other weight loss programs are effective in improvement of NASH/NAFLD, but are significantly most effective than non-surgical procedures such as, medical drugs and life style modifications. 41,77,78 Till now, the best surgical procedure for NAFLD/NASH is not determined and meta analyses, show that all bariatric surgical procedures lead to NAFLD/NAFLD improvement in obese patients and liver steatosis in most of this patients (near 90%). 47,64,70,79 Recent studies demonstrated that bariatric surgery; result in improvement of biochemical and histologic parameters of liver, such as non-alcoholic steatosis and steatohepatitis, liver fibrosis, lobular inflammations, chronic portal inflammations and even hepatocellular carcinoma.…”
Section: Selecting the Most Suitable Bariatric Procedures In Treatmentmentioning
confidence: 99%